2023
DOI: 10.26418/jtllb.v11i1.58766
|View full text |Cite
|
Sign up to set email alerts
|

Kesediaan Menggunakan Layanan oleh Penduduk Terhadap Fasilitas Sistem Pengelolaan Air Limbah Domestik Terpusat (SPALD-T) Perumahan Kosgoro Permai

Abstract: Pencemaran lingkungan akibat air limbah domestik merupakan permasalahan yang hingga saat ini masih menjadi fokus utama berbagai pihak. Berbagai upaya telah dilakukan untuk mengatasi permasalahan tersebut, satu diantaranya ialah melalui Sistem Pengelolaan Air Limbah Domestik Terpusat (SPALD-T). Kesediaan penduduk menggunakan layanan penting untuk diperhatikan dalam sebuah perencanaan, sehingga penelitian dilakukan dengan tujuan untuk mengetahui kondisi pembuangan air limbah domestik dan kesediaan penduduk mengg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…The 20meter buffering from the water bodies is an approximation to determine the communities that dispose of waste in the water bodies and those that do not. The basis for this distance determination comes from the research conducted by (Afifa Maharani et al, 2023), which showed that 100% of communities within that radius disposed of waste.…”
Section: Results and Discussion The Number Of People Disposing Of Wastementioning
confidence: 99%
“…The 20meter buffering from the water bodies is an approximation to determine the communities that dispose of waste in the water bodies and those that do not. The basis for this distance determination comes from the research conducted by (Afifa Maharani et al, 2023), which showed that 100% of communities within that radius disposed of waste.…”
Section: Results and Discussion The Number Of People Disposing Of Wastementioning
confidence: 99%